Application of transcranial Doppler in cerebrovascular diseases - Wan, Yuxiao; Teng, Xiufei; Li, Shiyi; Yang, Yanchao (Frontiers in Aging Neuroscience, 2022)
Transcranial Doppler (TCD) is a rapid and non-invasive diagnostic technique that can provide real-time measurements of the relative changes in cerebral blood velocity (CBV). Therefore, TCD is a useful tool in the diagnosis and treatment of clinical cerebrovascular diseases (CVDs). In this review, the basic principles of TCD and its application in CVD were outlined. Specifically, TCD could be applied to evaluate occlusive CVD, assess collateral circulation in patients with ischemic stroke, and monitor cerebral vascular occlusion before and after thrombolysis as well as cerebral vasospasm (VSP) and microembolization signals after aneurysmal subarachnoid hemorrhage (SAH). Moreover, TCD could predict short-term stroke and transient cerebral ischemia in patients with anterior circulation occlusion treated with endovascular therapy and in patients with anterior circulation vascular occlusion. Additionally, TCD not only could monitor blood velocity signals during carotid endarterectomy (CEA) or carotid artery stenting (CAS) but also allowed earlier intervention through early recognition of sickle cell disease (SCD). Presently, TCD is a useful prognostic tool to guide the treatment of CVD. On the one hand, TCD is more commonly applied in clinical research, and on the other hand, TCD has an increasing role in the management of patients. Collectively, we review the principles and clinical application of TCD and propose some new research applications for TCD.